Engineering properties and structural performance of rubberized concrete paving blocks - Ling, Tung Chai (2008)
Waste tyres could be utilized as partial replacement in order to preserve natural resources such as sand and to prevent the environment from further damage due to improper disposal of the tyres. There also been considerable research and development in the use of high toughness recycled tyres in concrete mixture to improve some engineering properties. In response to these demands, series of investigations were conducted and divided into three major parts in this project. For Part I, the laboratory trials were conducted to study the correlation between rubberized concrete paving blocks (RCPB) mixtures at different percentages of crumb rubber, water-cement ratio and strength. The effects of crumb rubber size, cement content and dosage of styrene-butadiene rubber latex were also investigated. To promote a practical use and acceptance of using RCPB by potential end users, Part II was carried out to investigate the manufacturing processes and the feasibility of producing RCPB in a commercial plant setting. A total of 4,300 RCPB containing 10% (10-RCPB), 20% (20-RCPB) and 30% (30-RCPB) of rubber and control concrete paving blocks (CCPB) were produced and tested for voids, abrasion, sound absorption, skid resistance, scanning electron microscopy, and long-term strength development in compression, flexural and splitting-tensile. The effect of compressive strength under three curing conditions of RCPB was also assessed. A relationship for the strength development between compression, flexural and splitting-tensile was therefore established. In Part III of this study, Highway Accelerated Loading Instrument (HALI) was developed. The concept of HALI development, including design, fabrication, calibration and performance monitoring, is also presented. RCPB pavement was tested with HALI and subjected to 10,000 cycles of load repetition. Additional tests, including shear resistance, skid resistance, and impact resistance were also conducted in order to have a better understanding of the effects of RCPB on the pavement behaviour. Results obtained from threedimensional models showed CCPB tend to yield slightly better than other types of RCPB. Despite better skid resistance and interlocking force of CCPB, the other types of RCPB containing crumb rubber showed a great improvement in toughness. The plant manufactured RCPB can be categorized as high strength and low toughness (CCPB); high strength and moderate toughness (10-RCPB); low strength and high toughness (20-RCPB and 30-RCPB). Therefore, all types of RCPB can be introduced to various types of pavement according to the traffic volume and the application of the pavement.